Petrography and geochemistry of intrusive magmas in Varmaqan – Sardare ghobadi in the west of Iran - Davari, Negin; Ali Arian, Mohammad; Ashja Ardalan, Afshin; Reza Jafari, Mohammad (Nexo Revista Científica, 2020)
The study area is a quadrilateral of 155 km2 between eastern longitude 47˚ and 40 ′ to 47˚ and 52 ′ and northern latitudes 35˚ and 00 ′ to 35˚ and 04 ′ that is located in west of Iran, north of Sonqor city and between Varmaqan and Sardare Ghobadi villages of Kermanshah province. In this range, the intrusive rocks are alkaline granite, granite, granodiorite, tonalite, quartz alkaline syenite, quartz monzonite, quartz monzodiorite, quartz diorite, alkaline syenite, monzonite, diorite, gabbro diorite, gabbro, and olivine gabbro as they were injected in the iron ores of cretaceous which has resulted in contact metamorphism and created hornfels at the site of contact. After comprehensive sampling of all required igneous rocks and according to the thesis objectives, thin sections were prepared and after petrography and some samples were selected for geochemical experiments. XRF analysis, ICP and alkaline fusion were performed on some samples. According to geochemical and petrological studies, the magmas forming these intrusive igneous rocks are from one region and because of magmatic differentiation or fractional crystallization, they from basaltic to acidic terms. Samples of this quadrilateral have a meta-alumina nature and granitoids are in the range of arc islands granites, continental arc granitoids and continental collision granitoids. The mineralogical and chemical composition of the acidic rocks in the area show that the granites in this study are type I.